Global Spore Sampling Project: A global, standardized dataset of airborne fungal DNA - Ovaskainen, Otso; Abrego, Nerea; Furneaux, Brendan; Hardwick, Bess; Somervuo, Panu; Palorinne, Isabella; Andrew, Nigel R.; Babiy, Ulyana V.; Bao, Tan; Bazzano, Gisela; Bondarchuk, Svetlana N.; Bonebrake, Timothy C.; et al. (Springer Nature, 2024)
Novel methods for sampling and characterizing biodiversity hold great promise for re-evaluating patterns of life across the planet. The sampling of airborne spores with a cyclone sampler, and the sequencing of their DNA, have been suggested as an efficient and well-calibrated tool for surveying fungal diversity across various environments. Here we present data originating from the Global Spore Sampling Project, comprising 2,768 samples collected during two years at 47 outdoor locations across the world. Each sample represents fungal DNA extracted from 24 m3 of air. We applied a conservative bioinformatics pipeline that filtered out sequences that did not show strong evidence of representing a fungal species. The pipeline yielded 27,954 species-level operational taxonomic units (OTUs). Each OTU is accompanied by a probabilistic taxonomic classification, validated through comparison with expert evaluations. To examine the potential of the data for ecological analyses, we partitioned the variation in species distributions into spatial and seasonal components, showing a strong effect of the annual mean temperature on community composition.